Pergerakan sosial ditinjau dari rasa kepemilikan masyarakat lokal (Studi kasus destinasi wisata alam bur telege desa hakim bale bujang kab. Aceh Tengah) - risa sanira risa (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
ABSTRACT The social movements carried out by the local community were motivated by immoral acts that violated the customary rules of the Gayo Sumang tribe caused by the construction of a Gayo land monument/graffiti that did not have a master plan, resulting in negative views. the wider community to Bur Telege hill, Hakim Bale Bujang village. The purpose of this study was to find out how the background of the occurrence of social movements at the Bur Telege tourist location carried out by the local community of Hakim Bale Bujang Village and to find out how the impact felt by the surrounding community after carrying out social movements by changing immoral locations into tourist destinations. This study uses the theory of Sense Of Place which has three related indicators, namely Locale, Location and Sense Of Place. By using descriptive research methods with a qualitative approach and data collection techniques using interview instruments. Research subjects were taken through purposive sampling technique, totaling 07 research subjects. The results of the study indicate that the background of this social movement is based on a sense of ownership of the local community to the area/region to maintain a good name to maintain the customary rules of the Gayo Sumang tribe by carrying out a social movement to move locations. immorality becomes a tourist destination that has an impact on creative economic life among the surrounding community. Hakim Bale Bujang. From the results of this study, it can be concluded that with the presence of perburah on the hill of Bur Telege, immoral acts in that location will be reduced so that the Gayo tribal regulations can still be preserved and their good name, these changes also have an impact on the growth of the local community's creative economy. Suggestions from the research are to create natural tourist destinations that are far from immoral acts, then visitors who visit tourist destinations should pay attention to sharia customary law so that immoral acts do not occur. Keywords: Location, Sense of Ownership, Local Community, Social Movement